Corpos e saberes em movimento: as jovens dançarinas de funk da Barra do Ceará - Sousa, Francisca Lidiane Araújo de (2014)
This work aims to understand how young dancers of a funk music group experience their body, gender and sexuality and how their knowledge is built in this process through the social practices experienced by this group. The investigative process was based on qualitative research and ethnography as a way of being close to the researched reality. Observation, field note writing, interviews and group discussion sections were important tools to understand the young dancers’ speech, perceptions and their comprehension of their own actions. I perceived, by investigating their lives, that the way the young dancers experience their body, gender and sexuality is intimately linked to funk music and the social context where they are inserted, including marks of gender, race and social class. Funk music influence the young dancers’ way of life and is determined in the way how they comprehend and produce their bodies and how they build their learning about sexuality. Gender relations and sexual-affective experiences lived by the young dancers, as well as funk, are permeated by paradoxical tensions, since although the young dancers subvert hegemonic gender standards and ways of experiencing the sexuality, they present a speech endorsed by social gender standards. The young dancers show liberal sexual morality, since they experience sexual-affective practices that are considered deviant by our society such as early sexual initiation, the intensification of affective exchanges and parallel sexual practices. The funk music group is also an option for leisure time, sociability and future perspective, in view of the few possibilities that they have. They build and share knowledge about the body and sexuality through the sociability.